Introduction: epistemic contestations in the hybrid media environment. (3rd July 2022) - Valaskivi, Katja; Robertson, David G.
ABSTRACT: "Post-truth era" and "fake news" have been the talk of the day for around 10 years now. In our understanding, these terms are used to refer to the contestations of epistemic hierarchies in Western liberal democracies experiencing political shifts toward populist political style and polarization. The contestation takes many forms but is mainly expressed through digital media technologies and related social practices that contribute to the epistemic instability. In this introductory article for the special issue of Epistemic contestations in the hybrid media environment, we argue that the experienced "epistemic crisis" is not only a crisis of epistemic hierarchies and worldviews but also a crisis of knowledge production within epistemic institutions, including the academia. The aim of the special issue is to explore how a multiplicity of competing epistemologies interact and compete in the "post-truth" marketplace of ideas in online popular communication.